Influence of Aging Heat Treatment on Pitting Corrosion Resistance of Martensitic Stainless Steel - Assi, Abdullah Dhayea (Al-Khwarizmi Engineering Journal, 2021)
In this research is to study the influence of the aging heat treatment on the pitting corrosion resistance of martensitic stainless steel (MSS), where a number of specimens from martensitic stainless steel were subjected to solution treatment at 1100 oC for one hour followed by water quenching then aging in the temperatures range (500-750) oC for different holding times (1,5,10,15&20) hr. Accelerated chemical corrosion test and immersion chemical corrosion test were performed on samples after heat treatment. The results of the research showed that the pitting corrosion resistance is significantly affected by the aging temperature. Where found that the aging samples at a temperature of 500 °C have the highest rate of corrosion which may be due to an increase in the ratio of the Delta type ferrite (δ-ferrite) and very soft precipitates from other phases of heterogeneous form in the basic martensitic phase; which leads to increased corrosion rate, whereas aging samples in the temperature range (550–650) °C have the smaller rate of corrosion values, this is due to the high volumetric ratio of remaining austenite. The aging samples at temperatures above 650 °C show an average corrosion rate. It was also found that the type of pits resulting from both the chemical corrosion tests and their shape were not related to the ferrite type and the carbides present in the microstructure